Hydroclimatic variations reveal differences in carbon capture in two concurrent conifers in northern Mexico - González Cásares, Marcos; Pompa García, Marín; Venegas González, Alejandro; Dominguéz Calleros, Pedro; Hernández Díaz, José Ciro; Carrillo Parra, Artemio; González Tagle, Marco Aurelio (PeerJ Inc., 2019)
Forest ecosystems are considered among the largest terrestrial carbon sinks. The dynamics of forest carbon depend on where the carbon is stored and its responses to environmental factors, as well as the physiology of the trees. Thus, threatened forest regions with high biodiversity have great scientific importance, such as the Sierra Madre Occidental in Mexico. A comparative analysis of tree species can expand the knowledge of the carbon cycle dynamics and ecological processes in this region. Here, we examined the growth, wood density, and carbon accumulation of two threatened species (Pseudotsuga menziesii and Cupressus lusitanica) to evaluate their hydroclimatic responsiveness.